2017
DOI: 10.1111/jdv.14081
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary hyperhidrosis with oral anticholinergic medications: a systematic review

Abstract: Primary hyperhidrosis is a condition characterized by excessive sweating. Patients are treated off-license with oral anticholinergic medications and report adverse events associated with systemic anticholinergic interactions. This review assesses clinical evidence of efficacy, impact on quality of life and adverse events associated with oral anticholinergic therapy for primary hyperhidrosis. PRISMA guidelines were implemented to complete a systematic review (PROSPERO:CRD42016036326). MEDLINE, EMBASE and PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 34 publications
2
86
1
1
Order By: Relevance
“…Although not yet FDA approved, systemic oral therapies are best suited for resistant cases unresponsive to topical nonsurgical approaches. 11,50 They operate in a variety of ways to systemically prevent stimulation of the eccrine sweat glands, limiting overall sweating. Anticholinergics are the most commonly prescribed oral agents, although antihypertensive and psychotropic drugs have also been utilized.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Although not yet FDA approved, systemic oral therapies are best suited for resistant cases unresponsive to topical nonsurgical approaches. 11,50 They operate in a variety of ways to systemically prevent stimulation of the eccrine sweat glands, limiting overall sweating. Anticholinergics are the most commonly prescribed oral agents, although antihypertensive and psychotropic drugs have also been utilized.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Various forms of treatment have been approved for HH, according to the part of the body affected, but in many cases good control of the condition is not achieved, either due to its intensity or because it affects various locations and cannot be addressed in a comprehensive way. In recent years, studies have demonstrated the effectiveness and safety of oral anticholinergics and especially of oral oxybutynin (OOx), which has been corroborated by clinical trials . Most studies in this respect, however, do not conduct follow‐up for more than 1 year and only evaluate effectiveness and adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A review of oral anticholinergic therapy for hyperhidrosis indicated that 40% of subjects in clinical studies withdraw from the treatment due to AEs. 9 Consequently, developing topical anticholinergic drugs is an ideal approach to treat hyperhidrosis as sweat glands are surrounded with cholinergic sympathetic nerves. Moreover, systemic effects may be mitigated by the reduced plasma drug levels seen with topical application.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that topical administration of UMEC could block stimulation of muscarinic receptors by acetylcholine and thereby reduce the overproduction of sweat. Precedents for this approach exist with systemic anticholinergic compounds 8,9 and with topical glycopyrrolate, 10 a pan-active muscarinic receptor antagonist with similar potency to UMEC, supporting both the validity of the mechanism and the route of administration. To date, no topical anticholinergic compound has received regulatory approval for the treatment of hyperhidrosis; UMEC has the potential to provide a safe, well-tolerated and efficacious topical treatment alternative to current modalities in patients who suffer from hyperhidrosis.…”
Section: Introductionmentioning
confidence: 99%